Firm Network Position and Corporate Venture Capital Investment. (6th August 2013) - Noyes, Erik; Brush, Candy; Hatten, Ken; Smith‐Doerr, Laurel; Karatas‐Ozkan, Mine; Anderson, Alistair R.; Fayolle, Alain; Howells, Jeremy; Condor, Roland
<x xml:space="preserve">Abstract</x> This study investigates why some firms have been more likely to make corporate venture capital investments than others. We anchor this study within a social networks perspective and prior network research that shows that information about business practices diffuses unevenly through interlocking boards, thereby influencing the corporate adoption of novel business practices. Using annual data on interlocking boards and corporate venture capital investments for S&P500 companies for the years 1996–2006, we show that a firm's corporate venture capital investment behavior can be predicted by its cumulative access to information about corporate venture capital practices gained through interlocking boards.